An investigation into the factors influencing the outsourcing decision of e-banking services: A multi-perspective framework. (20th February 2017) - Hanafizadeh, Payam; Zare Ravasan, Ahad
Abstract : Purpose: This paper aims to provide an in-depth analysis toward understanding the critical factors in affecting information technology outsourcing (ITO) decision in the context of e-banking services in Iran. Within the recent decades, outsourcing IT processes and services as a strategic decision has been widely adopted throughout industries. In this regard, scholars have investigated a wide range of factors influencing ITO decision in various contexts. Design/methodology/approach: This research examines a conceptual model that shows impacts of different attributes including technological, organizational and environmental on the Iranian banks' ITO decision. To validate the research hypotheses, the partial least squares (PLS) technique for data analysis, is utilized. Findings: The results of this study derived from the theoretical discussion of hypotheses illustrated that 9 of 11 assumed factors (i.e. perceived tangible benefits, perceived intangible benefits, perceived risks, perceived information security/privacy, complete contract establishment capability, making strong trustworthy relationship capability, uncertainty in business requirements, external pressure and market maturity) influence ITO decision in the target industry. The findings also confirmed that the size of the bank and competitors' absorptive capacity did not exert any influence on their service outsourcing decision. Research limitations/implications: The sampling was confined to experts in the banking industry. Also, the results of this study reflect Iranian perspective. Consequently, generalization based on this sample would be interpreted cautiously and a limitation of the context should be kept in mind. Originality/value: Insights into policymaking for suitable drivers to outsource e-banking services in the context of a less developed country are the main outcomes of the current research.